2021
DOI: 10.1093/ndt/gfab082.0041
|View full text |Cite
|
Sign up to set email alerts
|

Mo387clinical Performance, Hemocompatibility and Safety of a New Dialyzer With a Modified Polysulfone Membrane

Abstract: Background and Aims Hemodialyzers containing membranes made from a blend of polysulfone and polyvinylpyrrolidone (PVP) are widely used. PVP makes the membrane material more hydrophilic to reduce interactions with plasma proteins and platelets. A modified spinning technique has been established to stabilize the PVP on the blood-side surface in the polysulfone dialysis membrane in the new dialyzer FX CorAL 600. The objective of the present study was to prove for this new dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In summary, these β2-microglobulin results support previous findings that the hydrophilic modification of the FX CorAL reduces protein adsorption to the membrane and stabilizes the performance over time [12,19,38]. Moreover, these experimental data are in line with previous clinical trials, which consistently showed the highest β2microglobulin removal as compared to other polysulfone-, polyethersulfone-, or cellulosebased dialyzers [37,[39][40][41].…”
Section: Impact Of Protein Adsorption On Middle Molecule Clearancesupporting
confidence: 89%
See 3 more Smart Citations
“…In summary, these β2-microglobulin results support previous findings that the hydrophilic modification of the FX CorAL reduces protein adsorption to the membrane and stabilizes the performance over time [12,19,38]. Moreover, these experimental data are in line with previous clinical trials, which consistently showed the highest β2microglobulin removal as compared to other polysulfone-, polyethersulfone-, or cellulosebased dialyzers [37,[39][40][41].…”
Section: Impact Of Protein Adsorption On Middle Molecule Clearancesupporting
confidence: 89%
“…These experimental studies are backed by four clinical studies (comPERFORM, eM-PORA, eMPORA II, and eMPORA III) [37,[39][40][41]. All studies investigated β2-microglobulin removal during HDF treatment as the primary outcome and compared the FX CorAL to other polysulfone-, polyethersulfone-, or cellulose-based dialyzers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three earlier clinical trials evaluated FX CorAL 600 during short treatment periods [ 11 , 19 , 20 ]. FX CorAL showed the highest β2-m removal rates (RR) as compared to synthetic and cellulose-based comparator dialyzers.…”
Section: Introductionmentioning
confidence: 99%